CDs (at) ZIF-8 composite antibacterial nano material and sterilization method

By developing the synergistic effect of CDs@ZIF-8 composite antibacterial nanomaterials and blue light, the problem of low antibacterial performance and efficiency in the existing technology was solved, efficient bactericidal effect was achieved, and excellent antibacterial preservation performance was shown in fruit preservation.

CN119699409APending Publication Date: 2025-03-28ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411758400.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when using photodynamic antibacterial materials, there are few studies on the synergistic effects of structural design and reactive oxygen production, resulting in low antibacterial performance and efficiency, and excessive use of traditional antibiotics leads to increased drug resistance.

Method used

A CDs@ZIF-8 composite antibacterial nanomaterial was developed to significantly improve antibacterial performance through blue light synergy, shorten the sterilization treatment time, and prepare nanofiber membranes using microfluidic gas spray spinning technology to be used to preserve fruits.

Benefits of technology

It significantly improves antibacterial performance, shortens the sterilization treatment time, realizes the synergistic sterilization performance of blue light and CDs@ZIF-8, and shows good antibacterial and fresh-preserving effects in fruit preservation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119699409A_ABST
    Figure CN119699409A_ABST
Patent Text Reader

Abstract

The invention discloses a CDs (at) ZIF-8 composite antibacterial nano material and a sterilization method. The CDs (at) ZIF-8 composite antibacterial nano material is combined with blue light irradiation at the same time for sterilization. The blue light and the CDs (at) ZIF-8 composite nanomaterial are cooperated to significantly improve the antibacterial performance, shorten the sterilization treatment time, and realize the synergistic interaction sterilization performance of the blue light and the CDs (at) ZIF-8.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fruit preservation, and in particular to a CDs@ZIF-8 composite antibacterial nano material and a sterilization method. Background Art

[0002] Microbial contamination poses a serious threat to food, environment and public health, and has attracted widespread attention. Traditionally, antibiotics are often used to control microbial growth, but overuse leads to increased resistance and loss of effectiveness, which may pose a threat to human health and the environment.

[0003] Photodynamic antimicrobial technology, as an effective disinfection technology, has been used in recent years to avoid the emergence of drug resistance. It has high safety, high-efficiency broad-spectrum antimicrobial properties, low energy consumption, low cost, and no carcinogenic byproducts. Therefore, photodynamic antimicrobial technology is expected to replace traditional antibiotics, control microbial contamination, and has broad application prospects. However, there are few studies on the structural design of photocatalytic materials or the synergistic effects between photosensitizers that promote the generation of reactive oxygen species (ROS) to enhance antimicrobial activity, and there is still a lot of room for optimization.

[0004] Carbon dots (CDs) have unique optical properties, low toxicity, good biocompatibility, low cost and easy preparation, and have been widely used in bioimaging, cell labeling, ion detection, anti-counterfeiting and optoelectronics. Due to their unique advantages, such as small size (<10 nm), high quantum yield, wide excitation spectrum and high charge transfer efficiency, CDs have broad application prospects in photocatalysis. In addition, based on their unique photovoltaic properties and extensive light-harvesting ability, CDs can be used as photosensitizers to generate ROS under light, induce oxidative stress, and achieve photodynamic antibacterial activity. However, CDs are prone to self-aggregation, which to some extent limits their photosensitivity and antibacterial effect.

[0005] Metal-organic frameworks (MOFs) are generally considered to be excellent carriers for encapsulating various active molecules or nanoparticles. However, most MOFs show weak photocatalytic properties due to their weak light absorption. ZIF-8 has attracted great attention due to its easy synthesis, large porosity and tunable pore size. However, due to its weak light absorption ability and fast recombination of photogenerated charges, ZIF-8 exhibits poor photocatalytic performance.

[0006] Encapsulating CDs in MOFs to obtain hybrid nanostructures may be a feasible method to improve the dispersibility of CDs and the photocatalytic performance of CDs and MOFs. Therefore, it is necessary to develop a dual photodynamic enhanced antibacterial material synergistically composed of CDs and ZIF-8 to replace traditional antibiotics, thereby avoiding the development of drug resistance and meeting its safe and efficient antibacterial needs in the fields of food, environment, and public health.

[0007] Patent CN 118285420 A provides an antibacterial carbon dot B-CDs, which has good water solubility, excellent antioxidant and antibacterial properties, and can significantly inhibit Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus, but only high concentrations of B-CDs can effectively inhibit the growth of Escherichia coli within 24 hours. Patent CN 117776158 A discloses an antibacterial carbon dot (TM-CDs) based on coordination functionalization and its preparation method and application, which has good antibacterial effect and can inhibit the growth of a variety of dominant spoilage bacteria in aquatic products. However, the antibacterial treatment time is relatively long (TM-CDs are coated after co-culture with bacteria for 12 hours), and the antibacterial efficiency needs to be improved. Patent CN114304249 A discloses an antibacterial carbon dot based on onion source, as well as a preparation method of the carbon dot and its application in the preservation of aquatic products. The raw materials for preparation are cheap and easy to obtain, and the preparation process is relatively simple. However, the minimum inhibitory concentration (MIC value) for Escherichia coli is 4 mg / mL, the required antibacterial concentration is relatively high, and the antibacterial performance is poor.

[0008] Fresh fruits suffer serious losses after harvest, with microbial infection being the main cause. Packaging is an important means to reduce post-harvest losses and maintain fruit quality, and plays a vital role in storage, transportation and marketing. Nanofibers have a specific high specific surface area, large porosity, excellent mechanical properties and adjustable structure. Based on the above advantages, nanofiber membranes have good application potential in fruit preservation packaging. Microfluidic air-jet spinning (MBS) is a technology that can produce nanofibers with high porosity and specific surface area. Compared with electrospinning, MBS technology has the advantages of fast processing speed, high energy efficiency and good safety, and has been applied to the study of fruit and vegetable preservation. However, there is no research on the use of MBS technology to manufacture safe and efficient photodynamic antibacterial nanofiber fresh-keeping packaging. Summary of the invention

[0009] The purpose of the present invention is to provide a CDs@ZIF-8 composite antibacterial nanomaterial and a sterilization method, which can significantly improve the antibacterial performance of the CDs@ZIF-8 composite nanomaterial through the synergistic effect of blue light and the sterilization treatment time, thereby achieving the synergistic sterilization performance of blue light and CDs@ZIF-8.

[0010] The technical solution adopted by the present invention to solve its technical problem is: A synergistic sterilization treatment method using blue light and CDs@ZIF-8 composite antibacterial nanomaterials is disclosed, wherein the CDs@ZIF-8 composite antibacterial nanomaterials are used in combination with blue light irradiation for sterilization.

[0011] The bactericidal concentration of CDs@ZIF-8 composite antibacterial nanomaterials was set at 50~400ug / ml, and the bactericidal time was 120~180min.

[0012] The objects of sterilization are water or fruit.

[0013] A method for preserving fruits by using a composite antibacterial nanomaterial of blue light and CDs@ZIF-8, comprising the following steps: (1) Polycaprolactone, ethyl cellulose and CDs@ZIF-8 composite antibacterial nanomaterials were added to trifluoroethanol and mixed to form a spinning solution, and CDs@ZIF-8 nanofiber membrane was prepared by microfluidic air jet spinning; (2) Wrap the nanofiber membrane on the surface of the fruit and irradiate it with blue light for 120-180 min; (3) Storing or packaging the fruit for sale.

[0014] Microfluidic air jet spinning technology is an existing technology. In the present invention, the microfluidic air jet spinning flow rate is 5 mL h -1 ; The air pressure is 0.115 MPa; The distance between the receiving net and the nozzle is 15 cm.

[0015] The concentration of CDs@ZIF-8 composite antibacterial nanomaterials in the spinning solution is 0.01-0.05 g / mL; the mass ratio of polycaprolactone to ethyl cellulose is 1.5~2:1, and the total concentration of polycaprolactone + ethyl cellulose is 0.1-0.15 g / mL.

[0016] CDs@ZIF-8 composite antibacterial nanomaterials were prepared by the following method: Step 1: Add urea and citric acid into deionized water, mix by ultrasonic to form a raw material solution, heat in a hydrothermal autoclave for reaction, cool to room temperature, collect the reaction solution, filter, dialyze, and dry to obtain CDs; Step 2: Add CDs to methanol and mix well to obtain CDs liquid, then add it to a methanol solution of anhydrous zinc acetate, ultrasonically disperse it, and then quickly inject the mixed liquid into a methanol solution of 2-methylimidazole, stir, centrifuge, and dry to obtain CDs@ZIF-8 composite antibacterial nanomaterials.

[0017] The present invention uses citric acid and urea as raw materials and adopts a one-step hydrothermal method to synthesize carbon dots.

[0018] In step 1, the mass ratio of urea to citric acid is 1:3-4; the final concentration of the raw material solution is 1.2-1.5 g / mL.

[0019] In step 1, the reaction temperature is 150-170° C., and the reaction time is 2-3 hours.

[0020] The concentration of CDs solution is 2~3 mg / mL, the concentration of anhydrous zinc acetate methanol solution is 35~38 mg / mL, and the concentration of 2-methylimidazole methanol solution is 280~290 mg / mL.

[0021] The volume ratio of CDs liquid: methanol solution of anhydrous zinc acetate: methanol solution of 2-methylimidazole = 35~45:8~12:35~45.

[0022] The CDs@ZIF-8 composite antibacterial nanomaterial of the present invention: on the one hand, CDs can improve the photoelectric performance and light absorption capacity of MOFs. On the other hand, MOFs have a large specific surface area and porosity, providing a favorable space for loading CDs, which can prevent CDs from aggregating and improve their stability. CDs and ZIF-8 are composited to construct an efficient dual photodynamic sterilization material.

[0023] In order to solve the problems that the existing antibacterial preparations are prone to cause bacterial resistance, and the antibacterial effect of carbon dots and their complexes under non-light is not ideal and the antibacterial treatment time is long, the present invention adopts a technical idea different from the antibacterial principle of the existing carbon dots and their complexes, and uses the coordination self-assembly method to prepare a dual photodynamic enhanced CDs@ZIF-8 composite nanomaterial, and the blue light synergizes the CDs@ZIF-8 composite nanomaterial to significantly improve the antibacterial performance, shorten the sterilization treatment time, and achieve the synergistic bactericidal performance of blue light and CDs@ZIF-8. In addition, the CDs@ZIF-8 composite nanomaterial is combined with blue light to be applied to the preservation of perishable fruits, which has good antibacterial and fresh-keeping properties.

[0024] The beneficial effects of the present invention are: 1. Aiming at the problem that the existing carbon dots and their composite materials have low antibacterial performance and efficiency, the present invention provides a new idea for synthesizing a new synergistic bactericidal preparation based on CDs and MOFs combined with blue light. CDs@ZIF-8 nanomaterials and blue light (450 nm) have a synergistic effect in composite bactericidal treatment. The synergistic value (T / E ratio) of Escherichia coli treated with blue light and CDs@ZIF-8 for 2 hours is 25704>1. There is no growth of Escherichia coli after 3 hours of composite treatment of blue light and CDs@ZIF-8, and its synergistic value tends to positive infinity. For Staphylococcus aureus, the synergistic value (T / E ratio) of blue light and CDs@ZIF-8 for 1 hour is 115. There is no growth of Staphylococcus aureus after 2 hours of composite treatment of blue light and CDs@ZIF-8, and its synergistic value tends to positive infinity.

[0025] 2. Compared with the antibacterial duration and bactericidal amount of existing CDs and their complexes, the bactericidal amount of the combined treatment of blue light and CDs@ZIF-8 is significantly improved, the bactericidal time and concentration are significantly reduced, and the low-concentration bactericidal efficiency is greatly improved. It only takes 2 hours of combined treatment of blue light and CDs@ZIF-8 (0.1 mg / mL) to kill 7.27 lg of Staphylococcus aureus, and 3 hours of combined treatment of blue light and CDs@ZIF-8 (0.4 mg / mL) can kill 7.63 lg of Escherichia coli.

[0026] 3. The CDs@ZIF-8 material prepared by the present invention combined with blue light treatment has excellent broad-spectrum antibacterial performance. The nanofiber membrane is prepared by microfluidic air-jet spinning and applied to the preservation of fruits. The nanofiber membrane has good biocompatibility and still retains the synergistic antibacterial properties of CDs@ZIF-8 combined with blue light treatment, and has good application prospects in the field of fruit preservation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the TEM image of CDs@ZIF-8 composite antibacterial nanomaterial; Figure 2 is the scanning electron microscope (SEM) image of CDs@ZIF-8 composite antibacterial nanomaterial; Figure 3 It is the elemental mapping of energy dispersive X-ray spectroscopy (EDX) of CDs@ZIF-8 composite antibacterial nanomaterials; Figure 4 The antibacterial experiment was conducted on Staphylococcus aureus (A) and Escherichia coli (B) under different illumination times, and the number of Staphylococcus aureus (C) and Escherichia coli (D) was changed. Figure 5 The effect of different concentrations of CDs@ZIF-8 nanocomposites on the colony growth of Staphylococcus aureus (A) and Escherichia coli (B). The number of Staphylococcus aureus (C) and Escherichia coli (D) is shown in Figure 2. Different letters (ag) indicate significant differences ( p <0.05); Figure 6 It is measured by NBT absorption under light conditions. 2− (A) RNO uptake assay 1 O2 (B) and determination by DPBF fluorescence probe 1 O2 (C) production under CDs@ZIF-8 treatment. Photooxidation rates of NBT (D), RNO (E), and DPBF (F) in different treatment groups. Reactive oxygen species in S. aureus and E. coli under light and dark conditions (G, scale bar = 50 μm). Quantification of intracellular reactive oxygen levels in S. aureus (H) and E. coli (I).

[0028] Figure 7 Transmission electron microscopy (TEM) images of Staphylococcus aureus and Escherichia coli treated with saline, CDs, ZIF-8, and CDs@ZIF-8 nanocomposites under dark and light conditions, respectively (scale bar = 200 nm) (D), * p <0.05,** p <0.01,***p <0.001.

[0029] Figure 8 CDs@ZIF-8 / PCL / EC nanofiber membrane S. aureus and E. coli Antibacterial properties of the 200 μg / ml 200 μg / ml 200 μg / ml (A). Cell densities of Staphylococcus aureus (B) and Escherichia coli (C). Different letters (ad) represent significant differences ( p <0.05).

[0030] Fig. 9 Figure 2 shows the inhibitory effect of CDs@ZIF-8 / PCL / EC nanofiber membrane on inoculated gray mold in strawberry (A) and the corresponding lesion diameter (B) under light and dark conditions. Different letters (ab) represent significant differences (p<0.05).

[0031] Fig.10 The morphological photos of strawberries in different treatment groups (A). The changes in L value (B), a value (C) and b value (D) of strawberries. The changes in pH value (E), soluble solids (TSS) (F), weight loss rate (G) and hardness (H) of strawberries in different treatment groups, * p <0.05 (D-CK: control group under dark conditions, L-CK: control group under light conditions, D-EP: PCL / EC-treated group under dark conditions, L-EP: PCL / EC-treated group under light conditions, D-CZ: 2.5% CDs@ZIF-8 / PCL / EC-treated group under dark conditions, L-CZ: 2.5% CDs@ZIF-8 / PCL / EC-treated group under light conditions). DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below through specific embodiments.

[0033] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.

[0034] Herein, fruits include but are not limited to strawberries, blueberries, mangoes, dragon fruits, peaches, bananas, apples, loquats, oranges, kiwis, bayberries, grapes, and the like.

[0035] In this article, the synergistic effect of bactericidal factors is determined by the T / E ratio, where T represents the theoretical survival rate, which is the product of the survival rates of each single factor; E represents the survival rate of microorganisms after the combined action; a T / E ratio greater than 1 indicates a synergistic effect ("Practical Tutorial on Hospital Disinfection" by Xu Shiai et al., page 30, Hebei Science and Technology Press, publication date: 20140630).

[0036] Example 1: In this example, citric acid and urea are used as basic raw materials to synthesize carbon dots by hydrothermal method. The specific process is as follows: (1) Weigh 0.3 g urea and 0.96 g citric acid and evenly distribute them in 10 mL deionized water. Ultrasonicate for 5 min.

[0037] (2) The homogeneous solution obtained in step 1 was then transferred to a polytetrafluoroethylene-lined autoclave and heated at 160°C for 2 hours.

[0038] (3) Collect the reaction solution and filter it through a 0.22 μm microporous filter to remove residual impurities.

[0039] (4) The solution filtered in step 3 was dialyzed for 48 h using a 1000 Da dialysis bag to obtain CDs. The dialysate was collected and dried to obtain CDs.

[0040] Example 2: In this example, citric acid and urea are used as basic raw materials to synthesize carbon dots by hydrothermal method. The specific process is as follows: (1) Weigh 0.3 g urea and 0.9 g citric acid and evenly distribute them in 10 mL deionized water. Ultrasonicate for 5 min.

[0041] (2) The homogeneous solution obtained in step 1 was then transferred to a polytetrafluoroethylene-lined autoclave and heated at 170°C for 2 hours.

[0042] (3) Collect the reaction solution and filter it through a 0.22 μm microporous filter to remove residual impurities.

[0043] (4) The solution filtered in step 3 was dialyzed for 48 h using a 1000 Da dialysis bag to obtain CDs. The dialysate was collected and dried to obtain CDs.

[0044] Example 3: In this example, citric acid and urea are used as basic raw materials to synthesize carbon dots by hydrothermal method. The specific process is as follows: (1) Weigh 0.3 g urea and 1.2 g citric acid and evenly distribute them in 10 mL deionized water. Ultrasonicate for 5 min.

[0045] (2) The homogeneous solution obtained in step 1 was then transferred to a polytetrafluoroethylene-lined autoclave and heated at 150°C for 3 hours.

[0046] (3) Collect the reaction solution and filter it through a 0.22 μm microporous filter to remove residual impurities.

[0047] (4) The solution filtered in step 3 was dialyzed for 48 h using a 1000 Da dialysis bag to obtain CDs. The dialysate was collected and dried to obtain CDs.

[0048] Example 4: Synthesis of ZIF-8 using a solvothermal method. The specific experimental process is as follows: (1) Add Zn(CH3COO)2 and 2-MeIM into methanol solution to make Zn 2+ The molar ratio of 2-MeIM was 1:70, and the mixture was vigorously stirred at room temperature for 30 min.

[0049] (2) The reaction solution in step 1 is centrifuged, the obtained solid is collected, and washed three times with methanol. The obtained solid is dried to obtain ZIF-8.

[0050] Example 5: Preparation method of CDs@ZIF-8 composite antibacterial nanomaterials. The specific experimental process is as follows: (1) Weigh 100 mg of CDs (prepared in Example 1) and add it to 40 mL of methanol to fully dissolve to form a CDs solution.

[0051] (2) Add the CDs solution in step 1 into 10 mL Zn(CH3COO)2 methanol solution (0.361 g dissolved in 10 ml methanol) and sonicate for 30 min to make it evenly dispersed.

[0052] (3) The mixed solution from step 2 was quickly injected into 40 mL of 2-MeIM methanol solution (11.350 g 2-MeIM dissolved in 40 ml methanol) and stirred vigorously at room temperature for 30 min.

[0053] (4) The reaction solution of step 3 was centrifuged, the obtained solid was collected, and washed three times with methanol. The obtained solid was dried in an oven at 60°C to obtain CDs@ZIF-8 nanoparticles.

[0054] Example 6: Preparation method of CDs@ZIF-8 composite antibacterial nanomaterials. The specific experimental process is as follows: (1) Weigh 70 mg of CDs (prepared in Example 2) and add them into 35 mL of methanol to fully dissolve to form a CDs solution.

[0055] (2) Add the CDs solution in step 1 into 8 mL of Zn(CH3COO)2 methanol solution (concentration 35 mg / mL) and ultrasonicate for 30 min to make it evenly dispersed.

[0056] (3) Rapidly inject the mixture from step 2 into 35 mL of 2-MeIM methanol solution (concentration 280 mg / mL) and stir vigorously at room temperature for 30 min.

[0057] (4) The reaction solution of step 3 was centrifuged, the obtained solid was collected, and washed three times with methanol. The obtained solid was dried in an oven at 60°C to obtain CDs@ZIF-8 nanoparticles.

[0058] Example 7: Preparation method of CDs@ZIF-8 composite antibacterial nanomaterials. The specific experimental process is as follows: (1) Weigh 135 mg of CDs (prepared in Example 3) and add it to 45 mL of methanol to fully dissolve to form a CDs solution.

[0059] (2) Add the CDs solution in step 1 into 12 mL Zn(CH3COO)2 methanol solution (concentration 38 mg / mL) and ultrasonicate for 30 min to make it evenly dispersed.

[0060] (3) Rapidly inject the mixed solution from step 2 into 45 mL of 2-MeIM methanol solution (concentration 290 mg / mL) and stir vigorously at room temperature for 30 min.

[0061] (4) The reaction solution of step 3 was centrifuged, the obtained solid was collected, and washed three times with methanol. The obtained solid was dried in an oven at 60°C to obtain CDs@ZIF-8 nanoparticles.

[0062] Embodiment 8: A synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterials is used, wherein CDs@ZIF-8 composite antibacterial nanomaterials are used in combination with continuous blue light irradiation for sterilization; the bactericidal concentration of the CDs@ZIF-8 composite antibacterial nanomaterial is set to 50ug / ml, and the sterilization time is 120min.

[0063] Embodiment 9: A synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterials is used, wherein CDs@ZIF-8 composite antibacterial nanomaterials are simultaneously used in combination with continuous blue light irradiation for sterilization; the bactericidal concentration of the CDs@ZIF-8 composite antibacterial nanomaterial is set to 400ug / ml, and the sterilization time is 180min.

[0064] Embodiment 10: A synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterials is used, wherein CDs@ZIF-8 composite antibacterial nanomaterials are simultaneously used in combination with continuous blue light irradiation for sterilization; the bactericidal concentration of the CDs@ZIF-8 composite antibacterial nanomaterial is set to 200ug / ml, and the sterilization time is 160min.

[0065] The following tests were all conducted using the CDs@ZIF-8 composite antibacterial nanomaterial prepared in Example 5 as a representative: Structural characterization of CDs@ZIF-8 composite nanomaterials: (1) Morphological characterization of the composites. TEM images of CDs, ZIF-8 and CDs@ZIF-8 were obtained using a transmission electron microscope (2100F, JEOL JEM, Japan) at an accelerating voltage of 120 kV. SEM images of the as-prepared samples were obtained at an accelerating voltage of 3 kV using a scanning electron microscope (Sigma 300, ZEISS, Germany) equipped with an energy dispersive X-ray spectrometer, and EDX images of the as-prepared samples were obtained at an accelerating voltage of 15 kV.

[0066] (2) Spectral characteristics of composite materials. The Fourier transform infrared spectra (FT-IR) of the samples were measured in the range of 400-4000 cm-1 at a resolution of 4 cm-1 using a Fourier transform infrared spectrometer (Nicolet iS20, Thermo Fisher Scientific, Massachusetts). The UV-visible spectra (UV-vis) of the samples were recorded at 800-200 nm using a UV-visible spectrophotometer (UV-2600, Shimadzu, Japan).

[0067] (3) XRD and XPS analysis of composite materials. XRD patterns of CDs, ZIF-8 and CDs@ZIF-8 were obtained on an X-ray diffractometer (SmartLab SE, Rigaku, Japan). X-ray photoelectron spectroscopy (K-Alpha, ThermoScientific, Massachusetts) was performed on a spectrometer equipped with a monochromatic Al K α X-ray source (1486.6 e V) with a spot size of 400 μm, an operating voltage of 12 kV, and a filament current of 6 mA. The samples were scanned at a pass energy of 150 e V (full spectrum scan, step size of 1 eV) and 50 eV (high resolution scan, step size of 0.1 eV) in a vacuum ( P < 10 -7 The analysis was performed at 400 mbar, and all peaks were charge-corrected using the C1s binding energy of 284.80 eV as the energy standard.

[0068] (4) Zeta potential analysis of composite materials. The Zeta potential of CDs, ZIF-8 and CDs@ZIF-8 samples was measured using a nanometer Zetasizer (Nano ZS90, Malvern Zetasizer, UK).

[0069] The CDs synthesized by the present invention are roughly spherical, uniformly dispersed, and exhibit clear lattice fringes, with a lattice spacing of 0.21 nanometers and an average particle size of 1.48±0.52 nanometers (test results of Example 1). ZIF-8 exhibits a dodecahedral structure (test results of Example 4) with an average particle size of 142.61±28.09 nanometers, which is consistent with the scanning electron microscope (SEM) image. The morphology of the CDs@ZIF-8 nanocomposite material (test results of Example 5) is substantially the same as that of ZIF-8, showing a multi-core-shell structure, in which multiple CDs ( Figure 1 , Figure 2 In addition, a small amount of CDs are distributed on the surface of ZIF-8. It is worth noting that the encapsulation of CDs leads to an increase in the particle size of ZIF-8, and the average particle size of CDs@ZIF-8 is 204.67±81.52 nm ( Figure 1 ). Elemental mapping images from energy dispersive X-ray spectroscopy (EDX) ( Figure 3 ) showed that C, N, O, and Zn elements were uniformly distributed in the CDs@ZIF-8 nanocomposites. These findings suggest that there is little aggregation of CDs in the ZIF-8 framework, which effectively improves their dispersibility.

[0070] Determination of photodynamic bactericidal activity of CDs@ZIF-8 composite antibacterial nanomaterials in synergy with blue light treatment: (1) The bacterial suspension was mixed with CDs, ZIF-8 and CDs@ZIF-8 NPs in a 96-well plate, and the concentrations of CDs, ZIF-8 and CDs@ZIF-8 NPs were all 400ug / ml. The control group used sterile saline instead of materials. For Escherichia coli and Staphylococcus aureus, after 0, 30, 60, 120, and 180 min of blue light irradiation, 100 μL of bacterial suspension was taken out and diluted in a decimal system with sterile saline. Then, 100 μL of diluted bacterial solution and original bacterial solution (undiluted) were evenly spread on LB agar plates, cultured in a 37°C incubator for 12 hours, and the number of bacteria was counted by colony counting.

[0071] Figure 4 A shows that under dark conditions, CDs, ZIF-8 and CDs@ZIF-8 nanocomposites have almost no antibacterial effect. Under light conditions, as the irradiation time increases, 180 minutes of blue light irradiation can eliminate 0.77 lg of Staphylococcus aureus, showing a weak antibacterial effect. However, CDs, ZIF-8 and CDs@ZIF-8 nanocomposites exhibit antibacterial effects under light. As the illumination time increases, the number of Staphylococcus aureus colonies decreases, indicating that CDs, ZIF-8 and CDs@ZIF-8 nanocomposites have certain photocatalytic activity. Figure 4As shown in C, the agar plate corresponding to the CDs@ZIF-8 nanocomposite material had no colony growth after 120 minutes of illumination, and was able to effectively eliminate 7.27 lg of Staphylococcus aureus, which was significantly higher than using CDs alone (reduction of 4.17 lg) or ZIF-8 (reduction of 2.94 lg). When irradiated for 180 minutes, the number of Staphylococcus aureus colonies of CDs and ZIF-8 decreased by 5.85 lg and 4.59 lg, respectively. These findings indicate that under illumination, the CDs@ZIF-8 nanocomposite material can eliminate Staphylococcus aureus in a short time and with high efficiency. In addition, the antibacterial effect of the prepared material on Escherichia coli was also studied ( Figure 4 B and D). Consistent with the results for S. aureus, CDs, ZIF-8, and CDs@ZIF-8 nanocomposites had almost no antibacterial activity under dark conditions. After 180 min of blue light irradiation, 0.64 lg of E. coli was eliminated, showing weak antibacterial activity. It is worth noting that after 180 min of light irradiation, no bacterial colonies grew on the agar plates corresponding to the CDs@ZIF-8 nanocomposites, reducing the colony count of E. coli by 7.63 lg. The antibacterial activity of CDs@ZIF-8 nanocomposites against E. coli was significantly higher than that of CDs (reduction of 3.12 lg) and ZIF-8 (reduction of 4.18 lg). The results showed that CDs@ZIF-8 nanocomposites had dual photodynamically enhanced antibacterial activity. CDs@ZIF-8 nanocomposites exhibited enhanced dual photodynamic antibacterial properties, indicating that they can produce a large amount of reactive oxygen species (ROS) under light irradiation, thereby effectively inactivating microorganisms.

[0072] The bactericidal effects of different treatments were compared, and the synergistic effect (T / E ratio) was calculated. The CDs@ZIF-8 nanomaterial and blue light (450 nm) had a synergistic effect in the combined bactericidal effect. The synergistic value (T / E ratio) of Escherichia coli treated with blue light and CDs@ZIF-8 for 2 hours was 25704>1, which had a significant synergistic effect; there was no growth of Escherichia coli after 3 hours of combined treatment of blue light and CDs@ZIF-8, and its synergistic value tended to positive infinity. For Staphylococcus aureus, the synergistic value (T / E ratio) of blue light and CDs@ZIF-8 for 1 hour was 115>1, which had a significant synergistic effect; there was no growth of Staphylococcus aureus after 2 hours of combined treatment of blue light and CDs@ZIF-8, and its synergistic value tended to positive infinity. The results are shown in the following table: Light exposure time / bacterial survival Comparison Pure Blu-ray Blu-ray+CDs processing Blue light + ZIF-8 treatment Blu-ray+CDs@ZIF-8 processing Dark+CDs@ZIF-8 treatment Synergistic value of blue light and CDs@ZIF-8 treatment (T / E ratio) Escherichia coli (2h) 7.63lg 7.21lg 6.51 lg 5.84 lg 2.72 lg 7.55 lg 25704 Escherichia coli (3h) 7.63lg 6.99lg 4.51 lg 3.44 lg 0 lg 7.53 lg Positive Infinity Staphylococcus aureus (1h) 7.27lg 7.02lg 7.01 lg 5.90 lg 4.68 lg 6.99 lg 115 Staphylococcus aureus (2h) 7.27lg 6.80lg 3.10 lg 4.33 lg 0 lg 6.98 lg Positive Infinity

[0073] (2) Escherichia coli and Staphylococcus aureus suspensions were mixed with different concentrations of CDs@ZIF-8 NPs (0-0.4 mg / mL), and the control group used sterile saline instead of the material. After a certain period of blue light treatment, 100 μL of the bacterial suspension was taken out and diluted with sterile saline according to the decimal method. Then, 100 μL of the diluted bacterial solution and the original bacterial solution (undiluted) were evenly spread on the LB agar plate and cultured in a 37°C incubator for 12 hours. The number of bacteria was calculated by colony counting.

[0074] Under light irradiation, the colony counts of Staphylococcus aureus and Escherichia coli decreased with the increase of the dosage of CDs@ZIF-8 composite nanomaterials ( Figure 5 ), the minimum bactericidal concentration of CDs@ZIF-8 for Escherichia coli is 400ug / ml, and that for Staphylococcus aureus is 100ug / ml. The photodynamic antibacterial performance increased with the increase in the dose of the nanocomposite. This enhancement may be due to the fact that the nanocomposite produces reactive oxygen species (ROS) as a photosensitizer. In addition, given its high specific surface area, the nanocomposite increases contact with the microbial cell wall, which may cause mechanical damage. In addition, the surface of the CDs@ZIF-8 nanocomposite is positively charged, enabling it to bind to microorganisms (negatively charged). The surface structure of the microorganism is then destroyed, leading to its death. This study also found that the antibacterial effect of the CDs@ZIF-8 nanocomposite on Staphylococcus aureus was better than that on Escherichia coli.

[0075] Determination of reactive oxygen species generation by CDs@ZIF-8 nanomaterials in combination with blue light treatment: (1) Determination of the types and rates of reactive oxygen species generated by CDs@ZIF-8 nanomaterials in combination with blue light treatment. The reactive oxygen species generated by CDs@ZIF-8 NPs were determined using fluorescent probes and colorimetric reactions. First, the colorimetric reaction of nitro blue tetrazolium (NBT) was used to detect superoxide anions (·O 2-) generation. Briefly, CDs@ZIF-8 (400 μg / mL) was mixed with 100 μg / mL of NBT. The mixed liquid was subjected to light and dark treatment, and the decrease in the absorbance of the solution at 259 nm was recorded every 15 min using a UV-visible absorption spectrophotometer. Then, the generation of singlet oxygen (1O2) was measured using a 1,3-diphenylisobenzofuran (DPBF) fluorescent probe. CDs@ZIF-8 (400 μg / mL) was mixed with 1,3-diphenylisobenzofuran (DPBF, 20 μM, DMSO as solvent), and the light absorption of the solution at 416 nm was measured every 10 s. Finally, p-nitrosodimethylaniline (RNO) was used to detect the generation of singlet oxygen (1O2). RNO (30 µM), imidazole (0.5 mM), and CDs@ZIF-8 (400 µg / mL) were mixed, and the decrease in the absorbance of the mixed liquid at 440 nm was recorded every 15 min.

[0076] (2) Determination of reactive oxygen species in Escherichia coli and Staphylococcus aureus. The bacterial suspension was co-cultured with CDs, ZIF-8 and CDs@ZIF-8 NPs under light and dark conditions. The control group was a light and dark treatment group without adding samples. After that, DHE red fluorescent dye (5 mM) was added to the cell suspension, mixed evenly by pipetting, and incubated at room temperature in the dark for 60 min. After incubation, the bacterial suspension was centrifuged and washed twice with PBS to remove the staining solution. Finally, the fluorescence intensity of ROS in the bacteria was detected using a confocal laser scanning microscope (CLSM).

[0077] CDs@ZIF-8 nanocomposites exhibited enhanced dual-photodynamic antibacterial properties, indicating that they could generate a large amount of reactive oxygen species (ROS) under light irradiation, thereby effectively inactivating microorganisms. In this study, the generation of ROS was detected by UV-visible absorption spectroscopy. 2− It reacts with NBT to form formamide and reduce the absorption peak of NBT at 259 nm. The reduction of the absorption peak represents ·O 2− formation. Figure 6 A shows that the NBT absorption peak gradually decreases with the extension of irradiation time, which indicates that the CDs@ZIF-8 nanocomposite can produce O under light. 2− It is worth noting that the ·O 2− The production rate was significantly higher than that of CDs or ZIF-8 alone ( Figure 6 D). Similarly, the RNO absorption spectrum was used to determine 1 O2 production. Imidazole and 1The peroxide intermediate RNO generated by the O2 reaction has a bleaching effect, resulting in a decrease in the absorption at 440 nm. The absorption at 440 nm gradually decreases with the extension of irradiation time, indicating that the CDs@ZIF-8 nanocomposite can produce 1 O2, and 1 The rate of O2 generation was significantly higher than that of CDs or ZIF-8 alone ( Figure 6 B and E). DPBF fluorescent probe was further used to detect reactive oxygen species. 1 O2 has high specificity; once 1 When O2 binds, DPBF will undergo irreversible oxidation, resulting in a decrease in the absorption intensity at 416 nm. Figure 6 C and F show that the absorption intensity of DPBF decreases rapidly with the extension of illumination time, indicating that the CDs@ZIF-8 nanocomposite produces 1 O2, and the photooxidation rate of DPBF was significantly faster than that of CDs and ZIF-8. These results reveal that CDs@ZIF-8 nanocomposites can produce a large amount of ·O 2− and 1 O2, and the production rate of ROS was significantly higher than that of CDs and ZIF-8 alone under light irradiation.

[0078] Subsequently, the intracellular ROS levels of bacterial cells treated with CDs@ZIF-8 nanocomposites were evaluated. Dihydroethidium (DHE) easily crosses the cell membrane and is oxidized by intracellular ROS to generate ethidium. Ethidium can be incorporated into chromosomal DNA, generating red fluorescence. The intensity of this fluorescence is directly related to the intracellular ROS levels of bacterial cells. Figure 6 G shows that under light conditions, CDs, ZIF-8, and CDs@ZIF-8 nanocomposite groups all exhibited red fluorescence in Staphylococcus aureus and Escherichia coli cells, indicating that they were able to induce bacterial cells to produce ROS and exhibit photodynamic antibacterial effects. In contrast, under dark conditions, the red fluorescence in Staphylococcus aureus and Escherichia coli cells was relatively weak and almost undetectable, indicating that the production of ROS under dark conditions was almost non-existent. This observation is consistent with the results of in vitro ROS assays. Figure 6 As shown in H and I, the fluorescence of CDs and ZIF-8 is relatively weak under illumination. However, the CDs@ZIF-8 nanocomposite group exhibits significantly enhanced red fluorescence under illumination ( p<0.001). In addition, the red fluorescence intensity induced by the CDs@ZIF-8 nanocomposite in Staphylococcus aureus was significantly higher than that in Escherichia coli, which was the same as the antibacterial results on agar plates. These results indicate that the combination of CDs and ZIF-8 can induce higher ROS levels. Therefore, the CDs@ZIF-8 nanocomposite exhibits enhanced photodynamic antibacterial properties.

[0079] Observation of bacterial morphology treated with CDs@ZIF-8 composite antibacterial nanomaterials and blue light: Transmission electron microscopy (H7650, Hitachi, Japan) was used to observe the bacterial morphology of Escherichia coli and Staphylococcus aureus in CDs, ZIF-8 and CDs@ZIF-8 NPs under light and dark conditions. The sample-treated bacterial suspension was centrifuged and fixed in 2.5% glutaraldehyde overnight, rinsed with PBS buffer (0.1M, pH 7.0) three times, 15 min each time. After that, the sample was fixed again in 1% osmium acid for 1.5 h. Subsequently, the osmium acid was rinsed with PBS buffer (0.1M, pH 7.2), and then the sample was dehydrated with 30%, 50%, 70% and 80% ethanol solutions, each for 15 min, and then dehydrated with gradient concentrations (90% and 95%) of acetone solution, each for 15 min. Finally, it was treated with pure acetone twice, each for 20 min. The sample was infiltrated with resin and dried at 70◦C for 12 h. Finally, the dried samples were sliced ​​and stained, and the bacterial morphology was observed by TEM.

[0080] Figure 7 The images showed that in the control group and the dark-treated group, Staphylococcus aureus and Escherichia coli maintained their typical spherical and rod-shaped structures, respectively. The bacterial cell membrane was relatively intact, and no cell membrane rupture was observed in the images. In contrast, after treatment with CDs, ZIF-8, and CDs@ZIF-8 nanocomposites under light, the bacterial cell membrane was damaged to a certain extent, resulting in leakage of cell contents. In addition, Staphylococcus aureus and Escherichia coli treated with CDs@ZIF-8 nanocomposites showed more obvious membrane rupture and leakage of cell contents, indicating that CDs@ZIF-8 nanocomposites may be more effective in destroying the integrity of bacteria, ultimately leading to bacterial lysis and death. These results are consistent with the plate count results, confirming that CDs@ZIF-8 nanocomposites have enhanced dual-photodynamic antibacterial effects compared with CDs and ZIF-8 alone.

[0081] Example 11: Preparation method of CDs@ZIF-8 / PCL / EC nanofiber membrane (1) In 10 mL of trifluoroethanol, 0.65 g of PCL particles, 0.35 g of EC powder, and 0, 0.1, 0.25, and 0.5 g of CDs@ZIF-8 NPs (prepared in Example 5) were added and stirred to prepare a spinning solution.

[0082] (2) The spinning solution prepared in step 1 was loaded into a syringe. The microfluidic air jet spinning machine (JNS-MS-SBS01, Nanjing Genesis New Materials Co., Ltd.) had a microfluidic air jet spinning flow rate of 5 mL h -1 ; The air pressure was 0.115 MPa; The distance between the receiving net and the nozzle was 15 cm. PCL / EC nanofibrous membranes containing different concentrations of CDs@ZIF-8 NPs were prepared, and the obtained nanofibers were named pure PCL / EC nanofibrous membrane, 1% PCL / EC / CDs@ZIF-8 nanofibrous membrane (0.1gCDs@ZIF-8NPs), 2.5% PCL / EC / CDs@ZIF-8 nanofibrous membrane (0.25gCDs@ZIF-8 NPs) and 5% PCL / EC / CDs@ZIF-8 nanofibrous membrane (0.5gCDs@ZIF-8 NPs).

[0083] Example 12: Preparation method of CDs@ZIF-8 / PCL / EC nanofiber membrane The difference between this embodiment and embodiment 11 is that: 1 g of PCL particles and 0.5 g of EC powder were added to 10 mL of trifluoroethanol. Other steps were the same as those in Example 11.

[0084] Example 13: Preparation method of CDs@ZIF-8 / PCL / EC nanofiber membrane The difference between this embodiment and embodiment 11 is that: 0.75 g PCL particles and 0.5 g EC powder were added to 10 mL trifluoroethanol. Other steps were the same as in Example 11.

[0085] The antibacterial activity was measured using the CDs@ZIF-8 / PCL / EC nanofiber membrane prepared in Example 11 as a representative: (1) Inoculate single colonies of Escherichia coli and Staphylococcus aureus into sterile LB medium, shake at 200 rpm for 12 h at 37°C, and then dilute the bacterial solution to 10^ 7-8 CFU·mL -1 .

[0086] (2) The PCL / EC / CDs@ZIF-8 nanofibrous membranes containing 0%, 1%, 2.5%, and 5% CDs@ZIF-8 NPs were cut into 2 mm × 2 mm squares.

[0087] (3) The film described in step 2 was added into 5 mL of Escherichia coli and Staphylococcus aureus solutions, respectively, and incubated for 3 h under dark and light conditions. A bacterial solution without the nanocomposite film was used as the control group.

[0088] (4) Take out 100 μL of the bacterial suspension in step 3 and dilute it in a gradient manner using sterile saline according to the decimal method. Then, evenly spread 100 μL of the diluted bacterial suspension and the original bacterial suspension (undiluted) on the LB agar plate, incubate in a 37 ◦C incubator for 12 hours, and calculate the number of CFU by colony counting.

[0089] (5) Determination of the in vivo antifungal activity of the nanofiber membrane. The ‘Hongyan’ strawberry was selected as the test object for the in vivo antifungal effect of the nanofiber membrane. A wound was pierced on the equatorial plane of the strawberry fruit with a sterile inoculation needle, and then a suspension of Botrytis cinerea spores (5 μL, 10 6 CFU·mL -1 ), and the wound was covered with a nanofiber membrane. The inoculated strawberry fruits were transferred to a constant temperature and humidity chamber (26°C, 75% RH) for 3 days, and the decay of the fruits was observed. The whole experiment was repeated 3 times, with each treatment including 4 replicates and each replicate containing 3 fruits.

[0090] like Figure 8 As shown in A, under dark conditions, PCL / EC and nanofibrous membranes containing CDs@ZIF-8 nanocomposites have almost no significant antibacterial properties, which is related to the fact that CDs@ZIF-8 nanocomposites produce almost no reactive oxygen species (ROS) under dark conditions. When the nanofibrous membrane containing CDs@ZIF-8 nanocomposites is exposed to light, its antibacterial effect is significantly improved, and the colony count on the plate is greatly reduced. It is worth noting that there is no colony count on the agar plate corresponding to the nanofibrous membrane containing only 1% CDs@ZIF-8 nanocomposites. S. aureus However, there was no growth on the agar plate corresponding to the nanofiber membrane containing 2.5% CDs@ZIF-8 nanocomposite. E. coli Among them, the nanofiber membrane containing 1% CDs@ZIF-8 nanocomposite can effectively eliminate 7.68 lg of S. aureus and 4.90 lg E. coli , while the nanofiber membrane containing 2.5% CDs@ZIF-8 nanocomposite can effectively remove 7.64 lg E. coli ( Figure 8BC). The results showed that the addition of CDs@ZIF-8 nanocomposites endowed the nanofibrous membranes with excellent antibacterial properties. In addition, the photodynamic antibacterial effect of the nanofibrous membranes containing CDs@ZIF-8 nanocomposites was better against Staphylococcus aureus than against Escherichia coli, which was consistent with the antibacterial results of CDs@ZIF-8 nanocomposites observed previously.

[0091] Rot caused by fungal pathogens is one of the main causes of postharvest losses in fruits and vegetables. In this study, we selected strawberry, a representative of perishable fruits, and used Botrytis cinerea ( B. cinerea ) suspension inoculated to evaluate the antifungal effect of the nanofibrous membrane in vivo. Fig. 9 A shows that under dark conditions, all groups had no significant antifungal effect. Under light conditions, the control group and PCL / EC nanofiber membrane group did not show significant antifungal activity ( Fig. 9 B). However, the nanofibrous membranes containing 1%, 2.5%, and 5% CDs@ZIF-8 nanocomposites showed significant antifungal effects compared to the control and PCL / EC nanofibrous membrane groups. These nanofibrous membranes effectively delayed the decay of strawberries by inhibiting the growth of Botrytis cinerea, thereby maintaining the quality of strawberries. Notably, the nanofibrous membranes containing 2.5% and 5% CDs@ZIF-8 nanocomposites effectively eradicated Botrytis cinerea, and the strawberries remained intact and clean without fungal growth. The results showed that CDs@ZIF-8 nanocomposites could produce a large amount of reactive oxygen species (ROS) under light irradiation, exhibiting a broad spectrum of antimicrobial activity. With the increase in the concentration of CDs@ZIF-8 nanocomposites, the ROS level increased, resulting in the effective photodynamic inactivation of Botrytis cinerea spores. Therefore, the nanofibrous membranes containing 2.5% CDs@ZIF-8 nanocomposites were selected for subsequent strawberry storage and preservation experiments.

[0092] This example uses the CDs@ZIF-8 / PCL / EC nanofiber membrane prepared in Example 11 to measure its storage and preservation effect on strawberries. Specifically, the physical and chemical indicators of strawberries during the storage period of 0-12 days are measured. The specific experimental and measurement process is as follows: (1) Selected 'Hongyan' strawberries with similar size and maturity and no mechanical damage or disease for the next experiment. The strawberry fruits were randomly divided into six groups: control group under light, control group under dark, PCL / EC treatment group under light, PCL / EC treatment group under dark, 2.5% PCL / EC / CDs@ZIF-8 treatment group under light, and 2.5% PCL / EC / CDs@ZIF-8 treatment group under dark. Then they were stored at 10°C and 90% RH for 12 days. The physiological quality of strawberry fruits was measured on the 0th, 3rd, 6th, 9th, and 12th days. Each group included three replicates, and each replicate had at least 12 fruits.

[0093] (2) Color difference measurement: A colorimeter (MiniScan XE Plus, HunterLab, Virginia, USA) was used to measure the color changes at four positions on the equatorial plane of the strawberry fruit, and the values ​​of L, a, and b were recorded.

[0094] (3) TSS determination: A portable handheld sugar meter (PR-101α, ATAGO, Japan) was used to record the TSS content of strawberry juice. Strawberry juice was obtained by squeezing the pulp and filtering.

[0095] (4) pH measurement: a digital pH meter (PB-10, Sartorius, Germany) was used to record the pH value of strawberry juice. Strawberry juice was obtained by squeezing the pulp and filtering.

[0096] (5) Weight loss rate determination: The initial weight of the strawberries and the weight after a certain period of storage were weighed using an electronic analytical balance.

[0097] (6) Hardness determination: The hardness of strawberry fruit was evaluated using a texture analyzer (TA-XT2i, Stable Micro Systems, UK) with a probe diameter of 2 mm. Two different locations on the equatorial plane were selected for each fruit for testing and the average value of the data was obtained. The maximum penetration force (N) exerted by the probe on the strawberry fruit was taken as the hardness of the fruit.

[0098] CDs@ZIF-8 / PCL / EC nanofiber membrane exhibited excellent photocatalytic antibacterial activity, proving its feasibility in strawberry preservation. This study explored the effect of nanofiber membrane on the appearance quality of strawberries. Fig.10 A shows that no significant differences in the appearance of the strawberries were observed during the first 3 days. By the 6th day, the strawberries in the control group showed partial rot and deterioration, while the nanofiber membrane-treated group showed no signs of rot. Between days 9 and 12, the degree of rot in all groups of strawberries increased under dark conditions, resulting in loss of edibility. However, the strawberries treated with the CDs@ZIF-8 / PCL / EC nanofiber membrane stored under light conditions maintained good quality and did not rot. The results further confirmed that the CDs@ZIF-8 nanocomposite has excellent dual photodynamically enhanced antibacterial properties, significantly extending the shelf life of strawberries.

[0099] The quality indicators of strawberries, such as external color, soluble solids (TSS), pH, weight loss and firmness, are important factors affecting consumers' acceptance of fresh fruits. The color changes of strawberries were analyzed using a colorimeter and no significant differences were found between the different treatments ( Fig.10 B–D). In addition, there were no significant differences in soluble solids and pH values ​​of strawberries under different treatments ( Fig.10E–F), indicating that the nanofiber membrane does not affect the appearance and nutritional quality of strawberries. Fig.10 G shows that under light conditions, the weight loss rate of the CDs@ZIF-8 / PCL / EC nanofiber membrane group on the 12th day was significantly lower than that of the control group (p<0.05). These results are attributed to the excellent photodynamic antibacterial activity of the CDs@ZIF-8 nanocomposite in the nanofiber membrane. It can effectively eliminate microorganisms attached to the surface of strawberries and reduce microbial contamination, thereby delaying the increase in weight loss rate. As the storage time increases, the hardness of the strawberries gradually decreases ( Fig.10 H). The hardness of strawberries treated with CDs@ZIF-8 / PCL / EC nanofiber membranes decreased the slowest, mainly because the CDs@ZIF-8 nanocomposite in the nanofiber membranes had excellent dual photodynamic antibacterial activity, which could reduce the damage of microorganisms to strawberries and give them better peel strength. Overall, CDs@ZIF-8 / PCL / EC nanofiber membranes have excellent preservation effects, mainly because they can effectively kill microorganisms on the surface of strawberries through the dual photodynamic enhancement effect, delay the increase in weight loss rate, reduce the decline in fruit hardness, and extend the shelf life of strawberries without negatively affecting the appearance and nutritional quality.

[0100] in conclusion In the present invention, CDs@ZIF-8 / PCL / EC nanofiber membrane was prepared using MBS technology and applied to the preservation of perishable fruits. The results showed that CDs were successfully encapsulated in the ZIF-8 cavity to synthesize CDs@ZIF-8 nanocomposite. CDs@ZIF-8 nanocomposite showed synergistically enhanced photodynamic antibacterial properties against Escherichia coli (elimination of 7.63 lg), Staphylococcus aureus (elimination of 7.27 lg) and Botrytis cinerea spores (elimination of 5 lg), which was much better than using CDs or ZIF-8 alone. The significant enhancement of antibacterial activity was due to the fact that the ordered pores of ZIF-8 provided a favorable space for the loading of CDs and improved the dispersibility of CDs. On the other hand, the combination of CDs and ZIF-8 promoted the interfacial electronic interaction and promoted the generation of reactive oxygen species (·O 2− and 1 O2) was produced. Subsequently, the CDs@ZIF-8 nanocomposite was uniformly incorporated into PCL / EC, and the MBS technology was used to manufacture CDs@ZIF-8 / PCL / EC nanofiber membrane with excellent photodynamic antibacterial function. Studies have shown that the CDs@ZIF-8 / PCL / EC nanofiber membrane can inhibit the proliferation of natural microbial flora under light conditions, thereby extending the shelf life of strawberries. Overall, our research provides new ideas for the photodynamic synergistic enhancement of antibacterial properties based on hybrid nanostructures of CDs and MOFs, and provides a safe and efficient packaging form for the preservation of perishable fruits.

[0101] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.

Claims

1. A synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterials, characterized in that: CDs@ZIF-8 composite antibacterial nanomaterials were used in combination with blue light irradiation for sterilization.

2. The synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterial according to claim 1 is characterized in that: The bactericidal concentration of CDs@ZIF-8 composite antibacterial nanomaterials was set at 50~400ug / ml, and the bactericidal time was 120~180min.

3. The synergistic sterilization treatment method of blue light and CDs@ZIF-8 composite antibacterial nanomaterial according to claim 1 is characterized in that: The objects of sterilization are water or fruit.

4. A method for preserving fruits using a composite antibacterial nanomaterial of blue light and CDs@ZIF-8, characterized in that: The steps include: (1) Polycaprolactone, ethyl cellulose and CDs@ZIF-8 composite antibacterial nanomaterials were added to trifluoroethanol and mixed to form a spinning solution, and CDs@ZIF-8 nanofiber membrane was prepared by microfluidic air jet spinning; (2) Wrap the nanofiber membrane on the surface of the fruit and irradiate it with blue light for 120-180 min; (3) Storing or packaging the fruit for sale.

5. According to the method of claim 4, the concentration of CDs@ZIF-8 composite antibacterial nanomaterial in the spinning solution is 0.01-0.05 g / mL; the mass ratio of polycaprolactone to ethyl cellulose is 1.5-2:1, and the total concentration of polycaprolactone + ethyl cellulose is 0.1-0.15 g / mL.

6. The CDs@ZIF-8 composite antibacterial nanomaterial according to claim 1 or 4, characterized in that: Prepared by the following method: Step 1: Add urea and citric acid into deionized water, mix by ultrasonic to form a raw material solution, heat in a hydrothermal autoclave for reaction, cool to room temperature, collect the reaction solution, filter, dialyze, and dry to obtain CDs; Step 2: Add CDs to methanol and mix well to obtain CDs liquid, then add it to a methanol solution of anhydrous zinc acetate, ultrasonically disperse it, and then quickly inject the mixed liquid into a methanol solution of 2-methylimidazole, stir, centrifuge, and dry to obtain CDs@ZIF-8 composite antibacterial nanomaterials.

7. The dual photodynamically enhanced CDs@ZIF-8 composite antibacterial nanomaterial according to claim 6, characterized in that: In step 1, the mass ratio of urea to citric acid is 1:3-4; the final concentration of the raw material solution is 1.2-1.5 g / mL.

8. The dual photodynamically enhanced CDs@ZIF-8 composite antibacterial nanomaterial according to claim 6, characterized in that: In step 1, the reaction temperature is 150-170° C., and the reaction time is 2-3 hours.

9. The dual photodynamically enhanced CDs@ZIF-8 composite antibacterial nanomaterial according to claim 6, characterized in that: The concentration of CDs solution is 2~3 mg / mL, the concentration of anhydrous zinc acetate methanol solution is 35~38 mg / mL, and the concentration of 2-methylimidazole methanol solution is 280~290 mg / mL.

10. The dual photodynamically enhanced CDs@ZIF-8 composite antibacterial nanomaterial according to claim 6, characterized in that: The volume ratio of CDs liquid: methanol solution of anhydrous zinc acetate: methanol solution of 2-methylimidazole = 35~45:8~12: 35~45.

Citation Information

Patent Citations

  • Preparation of onion-source bacteriostatic carbon dots and application of onion-source bacteriostatic carbon dots in preservation of aquatic products

    CN114304249A

  • Bacteriostatic carbon dots based on coordination functionalization and preparation method and application thereof

    CN117776158A